Hydrothermal synthesis, characterization, and photocatalytic performance of W-doped MoO3 nanobelts - Phuruangrat A. (2017)
© 2016, Springer Science+Business Media Dordrecht. Orthorhombic MoO 3 and W-doped MoO 3 nanobelts were successfully synthesized by a hydrothermal method. The effect of W dopant on the photocatalytic performance of W-doped MoO 3 nanobelts was studied. The phase, morphology, and oxidation state of the products were characterized by X-ray diffraction analysis, Fourier-transform infrared and Raman spectroscopy, scanning electron microscopy, transmission electron microscopy, and X-ray photoelectron spectroscopy. In this research, MoO 3 and W-doped MoO 3 exhibited the same phase and morphology of orthorhombic nanobelts with growth along the [001] direction, including detection of Mo 6+ , O 2− , and W 6+ in the 3 mol% W-doped MoO 3 sample. The photocatalytic performance of the as-synthesized MoO 3 and W-doped MoO 3 nanobelts was monitored through photodegradation of methylene blue (MB) under visible radiation. W-doped MoO 3 nanobelts showed better photocatalytic performance than pure MoO 3 . The 3 mol% W-doped MoO 3 photocatalyst exhibited very good visible-light-driven activity for photodegradation of MB, as high as 99 % within 60 min.